AKOMODASI DALAM KONFLIK SOSIAL PADA DIPLOMASI PEMBERIAN PISUKE LINTAS DESA: KAJIAN SOSIOLIGUISTIK - Abdul Muhid (LPPM Universitas Bumigora Mataram, 2019)
This research was done at two villages (Batujai and Seatanggor) in Praya Barat Distric, Lombok Tengah Regency. The aim is at interpreting the social activity whilst doing a local Tradition; giving Pisuke to family member of bride. This research uses qualitative interpretative analyses by using Giles Theory. The data taken through self-involving, recording, and pistening. The oject of research was conducted to “Giving diplomation Pisuke at Setanggor Village”. The result found that, there is internal accommodation and both parties converge each other.